PENGARUH PENDEKATAN SAINTIFIK TERHADAP HASIL BELAJAR ILMU PENGETAHUAN ALAM DAN SOSIAL MATERI SUMBER ENERGI SISWA KELAS IV UPTD SD NEGERI 2 FONTEIN KUPANG - Risaldi Tunu; Chintia M.P. Ati; Heryon Bernard Mbuik (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the low learning outcomes of students in the subject of Natural and Social Sciences (IPAS), especially energy source material in class IV UPTD SDN 2 Fontein Kupang. This problem is caused by the lack of implementation of a learning approach that actively involves students, so that students tend to be passive in the learning process. This study aims to determine the influence of scientific approaches on the learning outcomes of IPAS on energy source materials of grade IV students. The research method used is a quantitative approach with a pre-experimental type using a One Group Pretest-Posttest design. The sample population as well as the research was all grade IV students totaling 20 people with saturated sampling techniques. The instruments used were learning outcome tests given before and after (posttest) treatment. Data analysis was carried out using a t-test with the help of the SPSS program. The results of the study showed a significant improvement in student learning outcomes after applying the scientific approach. The average pretest score of 8.05 increased to 134.5 in the posttest. The results of the t-test showed that the tcal value was greater than the ttable with a significance level of 0.001 < 0.05, so an alternative hypothesis was accepted. Thus, it can be concluded that there is a significant influence of the use of scientific approaches on the learning outcomes of science students in grade IV on energy source materials at UPTD SDN 2 Fontein Kupang.